A restaurant-based intervention to promote sales of healthy children’s menu items: the Kids’ Choice Restaurant Program cluster randomized trial - Ayala, Guadalupe X. (BMC Public Health, 2016)
BACKGROUND: Away-from-home eating is an important dietary behavior with implications on diet quality. Thus, it is an important behavior to target to prevent and control childhood obesity and other chronic health conditions. Numerous studies have been conducted to improve children’s dietary intake at home, in early care and education, and in schools; however, few studies have sought to modify the restaurant food environment for children. This study adds to this body of research by describing the development and launch of an innovative intervention to promote sales of healthy children’s menu items in independent restaurants in Southern California, United States. METHODS: This is a cluster randomized trial with eight pair-matched restaurants in San Diego, California. Restaurants were randomized to a menu-only versus menu-plus intervention condition. The menu-only intervention condition involves manager/owner collaboration on the addition of pre-determined healthy children’s menu items and kitchen manager/owner collaboration to prepare and plate these items and train kitchen staff. The menu-plus intervention condition involves more extensive manager/owner collaboration and kitchen staff training to select, prepare, and plate new healthy children’s menu items, and a healthy children’s menu campaign that includes marketing materials and server training to promote the items. The primary outcome is sales of healthy children’s menu items over an 18-week period. In addition, dining parties consisting of adults with children under 18 years of age are being observed unobtrusively while ordering and then interviewed throughout the 18-week study period to determine the impact of the intervention on ordering behaviors. Manager/owner interviews and restaurant audits provide additional evidence of impact on customers, employees, and the restaurant environment. Our process evaluation assesses dose delivered, dose received, and intervention fidelity. DISCUSSION: Successful recruitment of the restaurants has been completed, providing evidence that the restaurant industry is open to working on the public health challenge of childhood obesity. Determining whether a restaurant intervention can promote sales of healthy children’s menu items will provide evidence for how to create environments that support the healthy choices needed to prevent and control obesity. Despite these strengths, collection of sales data that will allow comprehensive analysis of intervention effects remains a challenge. TRIAL REGISTRATION: NCT02511938